Utility of SUVmax on 18 F-FDG PET in detecting cervical nodal metastases. Issue 1 (December 2016) - Lim, Rebecca; Ramdave, Shakher; Beech, Paul; Billah, Baki; Karim, Md; Smith, Julian; Safdar, Adnan; Sigston, Elizabeth
Abstract Background The presence of cervical lymph node metastasis is an important prognostic factor for patients with head and neck squamous cell carcinomas (HNSCC). Accurate assessment of lymph node metastasis in these patients is essential for appropriate prognostic and management purposes. Here, we evaluated the effectiveness of the maximum standardized uptake value (SUVmax ) on positron emission tomography (PET) in assessing lymph node metastasis in HNSCC prior to surgery. Methods A retrospective review of 74 patients with HNSCC who underwent PET/CT prior to neck dissection were examined. Pre-operative PET/CT scans were reviewed by two experienced nuclear medicine physicians and SUVmax of the largest node in each nodal basin documented. These were compared with the histology results of the neck dissection. Results A total of 359 nodal basins including 86 basins with metastatic nodes were evaluated. A nodal SUVmax ≥3.16 yielded a sensitivity of 74.4 % and specificity of 84.9 % in detecting metastatic nodes. The nodal SUVmax /Liver SUVmax ratio was found on receiver operating characteristic (ROC) to be effective in detecting metastatic nodes with an area under ROC curve of 0.90. A nodal SUVmax /Liver SUVmax ratio ≥0.90 yielded a sensitivity of 74.1 % and specificity of 93.4 %. By comparison, visual inspection yielded sensitivities of 66.3 and 61.6 % in observers 1 and 2 respectively. The corresponding specificities were 77.7 and 86.5 %. Conclusions Nodal SUVmax and nodal SUVmax /liver SUVmax are both useful in the pre-operative detection of metastatic nodes with the latter being superior to visual inspection. The ratio is likely to be more useful as it corrects for inter-scanner variability.